Seller Strategies on eBay - Steve Anderson; Daniel Friedman; Garrett Milam; Nirvikar Singh (University of California, Economics Department, 2004)
This paper analyzes seller characteristics and choices in approximately 1000 eBay auctions for a particular model of PDA. Seller characteristics include frequency of selling, reputation, and the qualities of the product sold. Seller choices include the length of the auction, information provided about the product, starting price, and whether to use a âBuy it Now' option. We find that different types of sellers pursue systematically different strategies for how their items are offered, and we discuss the possible causes of these differences. For example, the two high volume sellers in our sample always use a combination of a âBuy it Now' with a low starting price, while the many less frequent sellers use an array of pricing strategies. In addition, more highly rated sellers were somewhat more likely to provide more detailed product information, as well as secure payment options.
Keywords: 330